THE SIGNIFICANCE OF INTERLEUKIN 2 IN THE DEVELOPMENT OF MULTIPLE MYELOMA - Muxamadalieva Gulchexra (International Scientific and Current Research Conferences, 2024)
Multiple myeloma (MM) is a malignancy characterized by the proliferation of plasma cells in the bone marrow. The pathogenesis of MM is complex and involves various cytokines, among which Interleukin 2 (IL-2) plays a critical role. This article aims to review the significance of IL-2 in the development and progression of MM. The focus will be on the molecular mechanisms by which IL-2 influences MM cell growth, survival, and interaction with the bone marrow microenvironment. Understanding the role of IL-2 in MM could provide insights into potential therapeutic strategies targeting this cytokine.